Fuzzy logic control of a magnetic ball system - Kashif, 1983-, author; Shahrum Shah Abdullah, author; International Conference on Control Instrumentation and Mechatronic Engineering (CIM09) (2nd: 2009: Melaka) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL